Replace <math><mstyle displaystyle="true"><mi>f</mi><mrow><mo>(</mo><mi>x</mi><mo>)</mo></mrow></mstyle></math> with <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> .

Interchange the variables.

Rewrite the equation as <math><mstyle displaystyle="true"><mfrac><mrow><mi>y</mi></mrow><mrow><mn>8</mn></mrow></mfrac><mo>-</mo><mn>7</mn><mo>=</mo><mi>x</mi></mstyle></math> .

Add <math><mstyle displaystyle="true"><mn>7</mn></mstyle></math> to both sides of the equation.

Multiply both sides of the equation by <math><mstyle displaystyle="true"><mn>8</mn></mstyle></math> .

Simplify both sides of the equation.

Cancel the common factor of <math><mstyle displaystyle="true"><mn>8</mn></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Simplify <math><mstyle displaystyle="true"><mn>8</mn><mo>⋅</mo><mrow><mo>(</mo><mi>x</mi><mo>+</mo><mn>7</mn><mo>)</mo></mrow></mstyle></math> .

Apply the distributive property.

Multiply <math><mstyle displaystyle="true"><mn>8</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>7</mn></mstyle></math> .

Replace the <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> with <math><mstyle displaystyle="true"><msup><mrow><mi>f</mi></mrow><mrow><mo>-</mo><mn>1</mn></mrow></msup><mrow><mo>(</mo><mi>x</mi><mo>)</mo></mrow></mstyle></math> to show the final answer.

Set up the composite result function.

Evaluate <math><mstyle displaystyle="true"><mi>g</mi><mrow><mo>(</mo><mi>f</mi><mrow><mo>(</mo><mi>x</mi><mo>)</mo></mrow><mo>)</mo></mrow></mstyle></math> by substituting in the value of <math><mstyle displaystyle="true"><mi>f</mi></mstyle></math> into <math><mstyle displaystyle="true"><mi>g</mi></mstyle></math> .

Simplify each term.

Apply the distributive property.

Cancel the common factor of <math><mstyle displaystyle="true"><mn>8</mn></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Multiply <math><mstyle displaystyle="true"><mn>8</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>7</mn></mstyle></math> .

Combine the opposite terms in <math><mstyle displaystyle="true"><mi>x</mi><mo>-</mo><mn>56</mn><mo>+</mo><mn>56</mn></mstyle></math> .

Add <math><mstyle displaystyle="true"><mo>-</mo><mn>56</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>56</mn></mstyle></math> .

Add <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> and <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> .

Since <math><mstyle displaystyle="true"><mi>g</mi><mrow><mo>(</mo><mi>f</mi><mrow><mo>(</mo><mi>x</mi><mo>)</mo></mrow><mo>)</mo></mrow><mo>=</mo><mi>x</mi></mstyle></math> , <math><mstyle displaystyle="true"><msup><mrow><mi>f</mi></mrow><mrow><mo>-</mo><mn>1</mn></mrow></msup><mrow><mo>(</mo><mi>x</mi><mo>)</mo></mrow><mo>=</mo><mn>8</mn><mi>x</mi><mo>+</mo><mn>56</mn></mstyle></math> is the inverse of <math><mstyle displaystyle="true"><mi>f</mi><mrow><mo>(</mo><mi>x</mi><mo>)</mo></mrow><mo>=</mo><mfrac><mrow><mi>x</mi></mrow><mrow><mn>8</mn></mrow></mfrac><mo>-</mo><mn>7</mn></mstyle></math> .

Do you know how to Find the Inverse f(x)=x/8-7? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.